Deviasi Kontrak dalam Proyek Konstruksi: Sebuah Analisis Berbasis Temuan Audit Kinerja Inspektorat Daerah Provinsi Sumatera Barat - Rahmat Fauzan; Benny Hidayat; Akhmad Suraji (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This research investigates the factors that contribute to deviations in the implementation of government construction projects through a case study approach in West Sumatra Province. This research is based on the primary secondary data, namely the West Sumatra Provincial Inspectorate Auditor Performance Audit Report from 2017 to 2021, totaling 15 (fifteen) Audit Reports (LHP). The findings of the inspection results are grouped into 3 (three) types of deviations based on the objectives of implementing a construction project, namely Cost, Quality, and Time. The results of the analysis show four dominant factors causing deviation. The first cause is contractor negligence, with a percentage of 16.13%, which highlights the problem of work implementation that is not by the contract. The second cause was negligence of the supervision consultant, with a rate of 11.29%. This included a lack of adequate supervision and producing reports that needed to reflect the actual conditions on the ground. Furthermore, the last two causes are the negligence of the Activity Technical Implementation Officer (PPTK) and the Commitment Making Officer (PPK), each with a rate of 29.03%. These two factors include problems in activity management and administration, as well as approval and payment processes that must be by the contract. Overall, the data indicates that administrative and managerial issues were the most dominant cause of deviations, at 58.06%.